Consumers Mobile Phone Brand Preferences of Local Made Brands to Global: Evidences from West Shoa Zone, Oromia Regional State, Ambo Town, Ethiopia - Geleta, Negash (International Journal of Marketing Research Innovation, 2020)
The study was conducted in Oromia regional state West Shoa Zone in Ambo Town in case of “Consumer The mobile phone Brand Preferences of Local Made Brands to Global”. Mobile phones are today can be considered as one of ingredient in the life of human beings. But due to rapid developments in technology, modernization and new innovations, there is a short lifecycle of mobile phone, which has a great impact on the manufacturers and retailers of such products.  Then this study aimed to investigate the factors effecting consumers Mobile brand preferences local to global. The study employed both descriptive and explanatory research design. The target populations of the study were the mobile phone users in Ambo town of West Shoa Zone Oromia regional state, Ethiopia. The data was collected from 385 respondents by using convenience sampling technique. For data analysis descriptive (mean & standard deviation) and inferential (t-test, correlation analysis, and multiple regressions) were employed. Based on analysis the result shows the significance difference of local brand & global.  In addition the result of regression shows all variables statistically significant except innovation, social status, and price. This was because consumers were not affording imported brands. Then, it can be concluded that there was a significant relationship between consumers local brand preference and global. Therefore, it can be recommended that marketers should sell innovative brands to satisfy the desire of consumers.